Technological Basis for Information Science in Brazil: A Scientometric Study - Araujo, Ronaldo F.; Oliveira, Marlene (Qualitative and Quantitative Methods in Libraries, 2017)
The current study aims to investigate the scientific research on the technological theme and thus understand the basis of its support. It aims to outline the profile of scientific literature on technology in LIS through a descriptive and quantitative research based on scientometric studies of scientific communication. The source of the research was the Referential Database of Information Science Periodical Articles (BRAPCI) using the terms 'computer', 'automation', 'information systems', „technology‟, „electronic‟, 'e', 'digital' and 'virtual' gathered to analyze the technological base area of 353 articles. Results indicated that the articles were published between 1972 and 2008, outlining the year of 2001 with the largest quantity (29) and a decreasing setting in the last decade. The journal with the highest number of publications is Information Science (166); 82% of the authors have up to 2 published articles on technology, indicating that the subject has no homogeneous group work nor research continuity; and the most recurrent terms are "information" and "systems" and "technology". Seven thematic domain groups that constitute the technological basis of the field were identified: the most representative of them is led by 'information systems', followed by 'digital and virtual library'; policy issues involving 'internet and network'; 'computer teaching librarianship'; 'automatic indexing', 'knowledge management, and electronic publishing'.